Hasil Analisa Beberapa Unsur Kimia Dalam Makanan Indonesia - Grecia Maharani (Jurnal Kimia dan Kemasan, 1977)
A screening study was conducted on the contents of the major elements, calcium, mgnesium, potassium and sodium, and the trace elements, arsenic, cadmium, cobalt, copper, iron, lead, manganese, selenium and zinc in eleven commonly consumed dried or canned seafoods and two terrestrial products available on the market in Jakarta.